Impact of nano‐SiCP and nano‐hBNP on the corrosion performance and fatigue behavior of Mg–Zn hybrid nanocomposites. Issue 3 (24th September 2022) - Krishnan, Parthiban; Lakshmanan, Poovazhagan; Annamalai, Gnanavelbabu
Abstract: Magnesium (Mg) alloys are characterized by their high specific strength, strong damping resistance, and poor performance against corrosion. This study attempted to evaluate the corrosion capability and fatigue behavior of Mg–Zn alloys reinforced with nanosized silicon carbide (SiC) and hBN particles. Initially, different combinations (1.0 wt% nano‐SiCP [fixed] and 0.5, 1.0, and 1.5 wt% nano‐hBNP ) of hybrid nanocomposites were synthesized through a stir‐ultrasonication casting process. The samples cut from the nanocomposites were subjected to salt spray, potentiodynamic polarization, tensile, and fatigue tests. The resistance to corrosion and fatigue characteristics of the monolithic alloy and hybrid nanocomposites were measured and compared. Due to the reduction in potential imbalance across the Mg‐α and I‐phases, the hybrid nanocomposites revealed enhanced corrosion performance as compared with the base alloy. The fatigue strength of the Mg–Zn alloy reinforced with 1% SiCP and 1.5% hBNP is about 94 MPa, which is 41% greater than the base alloy's fatigue strength. The scanning electron microscopy micrograph is helpful in investigating the microstructures of the corrosion, tensile, and fatigue‐tested samples. Abstract : Mg hybrid nanocomposites were developed by reinforcing nanosized silicon carbide SiC and hBN particles using an ultrasonic‐assisted stir squeeze casting technique. The corrosion resistance properties were examined by a salt spray test and potentiodynamic polarization tests. The fatigue life was calculated and compared with monolithic alloys. Mg hybrid nanocomposites have shown improved corrosion and fatigue resistance properties as compared to monolithic Mg–Zn alloys.